Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

(p ⇒ q) =(¬p ∨ q) proof

  1. Apr 2, 2015 #1
    Hi :smile: Im studying mathematical logic by a pdf file. But there is no proof about this therorem so I don't understand.. How to prove this?
  2. jcsd
  3. Apr 2, 2015 #2


    User Avatar
    Science Advisor
    Gold Member

  4. Apr 2, 2015 #3
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook